Improving preschooler’s adaptation through game-based technologies - Kilybaуeva, Gulnur; Kyyakbayeva, Ulbossyn; Izmagambetova, Raissa; Myshbayeva, Gulmira; Bekmagambetova, Roza; Nurgaliyeva, Saniya (Institute of Advanced Engineering and Science, 2025)
Preschool years are critical for a child’s future learning and development. One of the most important challenges when a child enters kindergarten is adaptation. Negative experiences during this period might affect a child’s adaptation to school and may have long-term consequences. Leveraging game-based technologies can transform early education, making it more engaging, personalized, and effective, thus ensuring better preparedness for formal schooling. This study evaluates the effectiveness of game-based technologies in improving the social, emotional, and cognitive adaptation of young children to preschool settings in Kazakhstan. By employing a comprehensive mixed-methods approach, this research provides robust evidence of the efficiency of game-based technologies in supporting young children's adaptation to preschool environments in Kazakhstan. The study included two groups of children: an experimental group (EG) (n=70) and a control group (CG) (n=70). The positive outcomes suggest that incorporating game-based learning into early childhood education can considerably improve the overall preschool experience, and better prepare children for future academic challenges. The study’s findings provide valuable guidance for educators looking to improve early childhood education.